2005
DOI: 10.6028/nist.ncstar.1-5g
|View full text |Cite
|
Sign up to set email alerts
|

Fire structure interface and thermal response of World Trade Center towers

Abstract: Certain commercial entities, equipment, products, or materials are identified in this document in order to describe a procedure or concept adequately or to trace the history of the procedures and practices used. Such identification is not intended to imply recommendation, endorsement, or implication that the entities, products, materials, or equipment are necessarily the best available for the purpose. Nor does such identification imply a finding of fault or negligence by the National Institute of Standards an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
(9 reference statements)
0
10
1
Order By: Relevance
“…The only loads that were applied to the structural model were derived from the thermal results and gravity. Though not addressed here, the transfer of thermal data to the structural model in cases where a single software package is used is very streamlined [26].…”
Section: Nonlinear Structural Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The only loads that were applied to the structural model were derived from the thermal results and gravity. Though not addressed here, the transfer of thermal data to the structural model in cases where a single software package is used is very streamlined [26].…”
Section: Nonlinear Structural Analysismentioning
confidence: 99%
“…This one-way coupling allows the solution of the thermal analysis to be completed first without consideration of the structural response. The structural analysis can be solved after reviewing and validating the thermal results [26].…”
Section: Thermal and Structural Fe Analysismentioning
confidence: 99%
“…The temperature-dependent thermophysical properties of steel (thermal conductivity, density, and heat capacity) are taken from Ref. 3. The concrete thermophysical properties (thermal conductivity, density, and heat capacity) are taken from Ref.…”
Section: Heat Transfer Modelmentioning
confidence: 99%
“…For concrete thermal conductivity the value is varied from 1.5 W/(m.K) at 25 o C to 1.00 W/(m.K) at 1200 o C and for specific heats it is from 880 J/(kg.K) at 25 o C to 1500 J/(kg.K) at 1200 o C. The lightweight concrete of the two specimens was designed for a density of 1600 kg/m 3 (100 pcf) at ambient temperature, which is different from that of the concrete reported by Prasad and Baum (2005). Therefore, for this analysis, the concrete density was reduced from 1600 kg/m 3 at 20 o C to 1300 kg/m 3 for 1200 o C. The reduction function was selected as those of the lightweight concrete used by Prasad and Baum (2005). Moisture content of concrete was obtained as 51 kg/m 3 , based on the reported 70% relative humidity, 0.23 chemically bound water, 237 kg (522lb) cement, and concrete water mix of 127 kg (281 lb).…”
Section: Materials Thermal Propertiesmentioning
confidence: 99%
“…As for concrete, thermal properties were derived from the study results reported by Prasad and Baum (2005). Appendix A of the report provides these properties at different temperatures for the lightweight concrete.…”
Section: Materials Thermal Propertiesmentioning
confidence: 99%